The role of rescue services in reducing the social tension level - Ella Mukhamedovna Kueva (Вестник Майкопского государственного технологического университета, 2023)
The article discusses the role of rescue services on reducing the level of negative social tensionassociated with economic, political, medical and biological crisis situations. An analysis of the phenomenon and the concept of "social tension" has been carried out, and forms of the reaction of the population to various kinds of crises revealed. Prolonged social tension is considered to provoke the onset of socially dangerous phenomena that can destabilize social development and cause entropic processes. Modern methods of diagnosing public dissatisfaction with various processes in the economy, politics, social sphere have been briefly described, which can enable the competent authorities to properly respond to emerging crisis phenomena, or level their consequences. Rescue services are considered to be competent bodies in the structure of the state; their activities are aimed directly at the prevention and elimination of the consequences of emergency situations. The research method is a theoretical analysis of the problem based on theoretical and empirical data from previous sociological, psychological and pedagogical studies. The main conclusions are that rescue services are an important factor in maintaining an optimal level of social tension, an effective means of reducing the possibility of the onset of socially dangerous phenomena, the main tool for eliminating the consequences of catastrophes, a guarantee of people's confidence that they will be provided with assistance in emergency situations, which significantly reduces the level of their anxiety, anomic, propensity to unmotivated actions of a destructive plan.